Potential of human deciduous periodontal ligament stem cells for use in hepatic lineage and their exosome application on hepatic injuries / Punitha R. Vasanthan - Punitha, R. Vasanthan (2020)
Introduction: Human deciduous periodontal ligament stem cells represent as another source of stem cells from the dental origin. These cells were shown to have multi-potential attributes and also self renewing ability. These easily accessible stem cells candidate could also resolve issues concerning ethical and compatability for the use in regenerative purposes. However, their efficiency towards hepatic lineage differentiation has not been addressed so far. Meanwhile, the main contributor for regenerative properties were supposedly mediated by soluble factors and extracellular vesicles such as exosomes secreted by cells. Objectives: The aims of this study are to isolate, characterize and also to investigate the propensity of stem cells derived from periodontal ligament towards hepatic lineage. Besides that, the emergence of cell free based treatment have prompted the study on exosomes derived from periodontal ligament stem cells and their relevance in hepatic injury. Methods: Periodontal stem cells derived from human deciduous tooth were isolated and characterized using the gold standard characterization method. Differentiation of periodontal ligament stem cells into hepatocyte-like cells were conducted by the exposure of two phases media induction. First phase was performed in the presence of Hepatocyte growth factors and Nicotinamide to induce a definitive endoderm formation. In the subsequent phase, the cells were treated with Oncostatin M, Dexamethosone and Insulin Transferrin to generate hepatocyte-like cells. Hepatic-related characters of the generated hepatocyte-like cells were determined at both mRNA and protein level. Furthermore, functional assay was conducted to examine the functionality of the hepatocyte-like cells. On the other hand, the extracellular vesicles components were characterized prior to the application into assisting in in vitro hepatic injury induced by hydrogen peroxide on HepG2 cells. Polymer based precipitation were employed to isolate iii exosomes and subjected to assessments on surface markers and protein quantification. Results: Foremost changes observed in the generation of hepatocyte-like cells were the morphological features in which these cells were transformed from fibroblastic shape to polygonal shape. Temporal expression of hepatic markers ranging from early endodermal up to late markers were detected in the hepatocyte-like cells. Differentiated periodontal ligament stem cells exhibited functional features of a hepatocyte during and at the end of the experiment duration. Crucial hepatic markers such as glycogen storage, albumin and urea secretion were also shown. In addition, exosomes isolated from periodontal ligament stem cells displayed positive exosome markers with correlation between cell confluence and exosome release. As for the in vitro hepatic injury, exosome from periodontal ligament stem cells conditioned media showed reduction in terms of HepG2 cells injuries after being exposed to oxidative stress. Conclusions: These findings exhibited the ability of periodontal ligament stem cells to be directed into hepatic lineage fate contributing towards usage beyond tooth regeneration. Along with that, the exosomes from periodontal ligament stem cells displayed hepatoprotective attributes in terms of reduction of oxidative stress. Ultimately, these cells can be regarded as an alternative autologous source potential not only for stem cell based treatment but also as a compelling alternative for non viable or cell free treatment in liver diseases. Keywords: periodontal ligament, stem cells, hepatocytes, exosomes